Two new xanthones from Calophyllum nodusum (Guttiferae) - Mad Nasir, Nadiah; Rahmani, Mawardi; Shaari, Khozirah; Ee, Gwendoline Cheng Lian; Go, Rusea; Kassim, Nur Kartinee; Mohamad, Siti Noor Kamilah; Che Jamil, Mohamad Johadi Iskandar (MDPI, 2011)
The air-dried powdered stem bark of Calophyllum nodusum (Guttiferea) collected from Sandakan (Sabah, Malaysia), was extracted sequentially with hexane, chloroform and methanol. The solvents were removed by rotary evaporator to give dark viscous extracts. Detailed and repeated chromatographic separation of the extracts lead to isolation of two new xanthones, identified as nodusuxanthone (1a) and trapezifolixanthone A (2). Other common terpenoids such as betulinic acid, lupeol, stigmasterol and friedelin were also isolated from the extracts and identified. The structures of the compounds were established by detailed spectral analysis and comparison with previously reported data.